2019
DOI: 10.3390/languages4030052
|View full text |Cite
|
Sign up to set email alerts
|

The Identity Construction of Migrants on Facebook

Abstract: Social network sites, such as Facebook, allow access to a series of resources or discursive forms that constitute a multimodal and dialogical system that transcends barriers of time and space, favouring transnational communication, something particularly important to migrants. In addition, the comments and dialogues that take place in such socialisation spaces allow us to develop a greater knowledge of the identity and positioning of the user with respect to others. With this work we analyse, from a qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Hence, while networking is maintained through WhatsApp or phone (AUE14; AUE15), most platforms are used to diffuse information only. As such, to the extent that young Uruguayans in Spain use social media to stay informed about Uruguay (Arocena & Zina, 2011, 26), these means might become not only a virtual transnational space where national identities are constructed (e.g., Mapelli, 2019) but also a potential bridge to connect emigrant generations.…”
Section: Uruguayans In Spainmentioning
confidence: 99%
“…Hence, while networking is maintained through WhatsApp or phone (AUE14; AUE15), most platforms are used to diffuse information only. As such, to the extent that young Uruguayans in Spain use social media to stay informed about Uruguay (Arocena & Zina, 2011, 26), these means might become not only a virtual transnational space where national identities are constructed (e.g., Mapelli, 2019) but also a potential bridge to connect emigrant generations.…”
Section: Uruguayans In Spainmentioning
confidence: 99%
“…Even when it is uttered in the Indonesian variety "sedap" (Indonesian: delicious), it is only used as expression of exclamation after having a delicious meal and not for asking the taste of prospective foods; in the latter context, the word is "enak" (Indonesian: delicious). In many cases, the use of the Malay language led to confusion for both parties, and switching to English was an effective strategy; however, the use of Malay, accentuating identities associated with the language (Mapelli 2019;Moustaoui Srhir et al 2019), might minimize social differentiation and increase solidarity (Bhatt and Bolonyai 2022) between the staff and clients as members of the same speech community, although they opt for English to avoid possible misunderstandings.…”
Section: Extract 4: Rembiga Satay (Nur and Arif Ln6-ln15)mentioning
confidence: 99%
“…Some studies have demonstrated the significance of new media outlets to shape and promote identities of im/migrants (Aguirre and Davies, 2015; Mapelli, 2019). Oiarzabal (2012), for example, discusses the emergence of Basque diaspora-association groups on Facebook and the ways that they utilize the web to fortify their communal identities.…”
Section: Migrant Workers On Facebookmentioning
confidence: 99%